Dampak Relokasi Terminal Terboyo Semarang Bagi Pengguna Terminal - Emaya Kurniawati; Wyati Saddewisasi (Journal on Education, 2023)
Terboyo Semarang Terminal is getting worse day by day due to tidal water that always inundates the terminal Terboyo Semarang. The existence of the terminal is needed by the community, so the government as a public servant continues to do various ways to make the terminal users feel comfortable. With the condition of the Terboyo terminal which is already less suitable for use as a passenger terminal, the Semarang City Government moved the Main Terminal located west of Semarang City, namely on Jl. Mangkang Raya Semarang in early 2016 with more complete facilities. With the passage of time, the Mangkang Terminal that has been provided by the government is not maximally used by traders, bus crews and passengers. In this study, the data from the research results were analyzed with qualitative methods by conducting direct observation or observation, interviews and documentation. from the results of interviews conducted by researchers, namely the bus crew and traders with the move of the terminal, the income received has decreased, which for the bus crew costs higher for diesel fuel and less time to rest. The use of this qualitative research aims to be more in-depth in understanding how much influence the terminal move has on traders, bus crews and passengers. The results of this research show an adverse impact, namely reduced income for bus crews, traders or sellers at the Terboyo terminal, while the impact on passengers is different, some feel benefited and some feel disadvantaged.